Eleven Densely Clustered Genes, Six of them Novel, in 176 kb of Mouse t-complex DNA - Kargul, George J.; Nagaraja, Ramaiah; Shimada, Tokihiko; Grahovac, Marija J.; Lim, Meng K.; Nakashima, Hiroshi; Waeltz, Paul; Ma, Peter; Chen, Ellson; Schlessinger, David; Ko, Minoru S.H. (Genome Research, 2000)
Targeted sequencing of the mouse t-complex has started with a 176-kb, gene-rich BAC localized with six PCR-based markers in inversion 2/3 of the highly duplicated region. The sequence contains 11 genes recovered primarily as cDNAs from early embryonic collections, including Igfals (previously placed on chromosome 17),Nubp2 (a fully characterized gene), Jsap1 (a JNK-binding protein), Rsp29 (the mouse homologue of the rat gene), Ndk3 (a nucleoside diphosphate kinase), and six additional putative genes of unknown function. With 50% GC content, 75% of the DNA transcribed, and one gene/16.0 kb (on average), the region may qualify as one of the most gene-dense segments in the mouse genome and provides candidates for dosage-sensitive phenotypes and mouse embryonic lethals mapped to the vicinity.[The sequence data described in this paper have been submitted to the GenBank data library under accession no. AF220294.]